Речные раки (Crustacea, Astacidae) Советского Союза. Сообщение V. Происхождение основных ареалов современных западнопалеарктических видов семейства Astacidae - Бродский, С.Я. (Вестник зоологии, 1977)
The Austropotamobius and Astacus genera from the Astacina subfamily and their smaller taxons from their reservation, the Neweuxin basin, immigrated to rivers in six groups. Depending on the degree of adaptation to salinity, getting over integrating ten vironment resistance», they penetrated to the regions of modern inhabitance of their ta xons and formed areas of distribution. A. (At.) italicus was the first to immigrate to the Danube.